Fixed-time disturbance observer based fixed-time back-stepping control for an air-breathing hypersonic vehicle. (May 2019) - Wang, Xiao; Guo, Jie; Tang, Shengjing; Qi, Shuai
Abstract: This paper proposes a fixed-time backstepping control scheme based on fixed-time disturbance observer for flexible air-breathing hypersonic vehicles. The backstepping control is combined with the fixed-time control technique to achieve fixed-time convergence. A fixed-time super-twisting disturbance observer, which is convergent independently of initial conditions, is employed to estimate and compensate the uncertainties and flexible effects in tracking process. A nonlinear first-order filter is adopted to avoid the "explosion of complexity" problem that arises in traditional backstepping, and to guarantee overall fixed-time stability. The closed-loop system is proven to be semi-globally uniformly ultimately fixed-time bounded via Lyapunov analysis. Simulation results are given to demonstrate the effectiveness of the proposed scheme. Highlights: A robust fixed-time back-stepping controller is designed for air-breathing hypersonic vehicles. A fixed-time super-twisting disturbance observer is proposed. A nonlinear first-order filter is introduced to eliminate "explosion of complexity" problem.